ANALISA V/C RATIO RUAS JALAN PANTURA DI KABUPATEN KENDAL PASCA BEROPERASINYA JALAN TOL BATANG – SEMARANG - Iwan Setiawan (Jurnal Teknik Indonesia, 2020)
The purpose of this final project is to calculate the volume of traffic passing the Cepiring - Kendal road section. The first is calculating the V / C Ratio on the Cepiring - Kendal road section after the operation of the Semarang - Batang toll road. Then compare the value of V / C Ratio on the pantura road Cepiring - Kendal before and after the operation of the Semarang - Batang toll road. In addition to the objective, the benefits of this final project are to determine the level of vehicle traffic density on Jalan Pantura, Kendal Regency after the operation of the Batang - Semarang Toll Road based on the existing traffic volume. Then it becomes a reference for Stake Holders to determine policies related to the density level of the Cepiring - Kendal Pantura road.Keywords: V / C Ratio; traffic density; traffic volume; pantura road